(untitled) (Raparin Journal of Humanities (RJH), 2025)
The research has mentioned the construction of language and its importance in transmitting purpose, Al’s indicated that without language meanings and purpose can’t be transferred to others. Then it is mentioned how Salem has described language of Qasida and the difference with the ghazal language Salm’s dictionary of Qasida one after one with its allusion in it, which each of them include a different sort of hint,has been shown.in one side, Salm’s religious Qasida s own special dictionary and linguistic characters that are symbols and his linguistic dictionary is linked to the religious subjects or patriotically that the dictionary of patriotic ones are mentioning wars, distruction of bloodshed and conquering of Kurdistan’s conquerer and the name of places, noble people,words and symbols are pure Kurdish and his describing Qasida indicate Baban leader’s bravery and knighthood or the greatness of Islam prophet, in other side، his social Qasida show good behaviors and bad habits and the words and allusions are in this circumstance. generally, the culture and language of the Qasida and the symbols in the Qasida are different according to the theme and purpose for which they are used.This tells us the fact that the dictionary (culture) of language and poetic symbols differ not only from poet to poet, but also from poet’s poems to another. Language of ghazal differ from Qasida and language of Qasida is different from hajoo and it’s purpose even from a Qasida to another according to the content.